2002
DOI: 10.1159/000066626
|View full text |Cite
|
Sign up to set email alerts
|

Proestrous Surge of Gonadotropin-Releasing Hormone Secretion Inhibits Apoptosis of Anterior Pituitary Cells in Cycling Female Rats

Abstract: Estrogen affects apoptotic cell death in estrogen-responsive tissues. The purpose of the present study was to examine dynamic changes in apoptotic cell death in the anterior pituitary gland during the estrous cycle and to investigate neuroendocrine regulation of these changes in cycling female rats. Terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) for in situ detection of DNA strand breaks revealed that the number of TUNEL-positive anterior pituitary cells was changing during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…sGC␣ 1 levels and timing of pituitary cell proliferation seem to be correlated. sGC␣ 1 expression raises on estrus and diestrus, while proliferation events are taking place, and remains low on proestrus, when the highest levels of apoptotic cells are detected (6,19,28). Thus the putative role of ␣ 1 in anterior pituitary cell renewal opens a very attractive landscape that is now under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…sGC␣ 1 levels and timing of pituitary cell proliferation seem to be correlated. sGC␣ 1 expression raises on estrus and diestrus, while proliferation events are taking place, and remains low on proestrus, when the highest levels of apoptotic cells are detected (6,19,28). Thus the putative role of ␣ 1 in anterior pituitary cell renewal opens a very attractive landscape that is now under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Massive release of GnRH is observed during the gonadotropin surge [29,30] and the period of elevated GnRH would be sufficiently long [30] so that GnRH could promote annexin A5 expression. This elevation of GnRH could also produce other cellular responses, including a reduction of a pro-apoptotic gonadotropes [31]. It is of interest to clarify the relationship between annexin A5 expression and gonadotrope-induced apoptosis during the afternoon of proestrus [31].…”
Section: Discussionmentioning
confidence: 99%
“…This elevation of GnRH could also produce other cellular responses, including a reduction of a pro-apoptotic gonadotropes [31]. It is of interest to clarify the relationship between annexin A5 expression and gonadotrope-induced apoptosis during the afternoon of proestrus [31]. On the other hand, GnRH may exert chronic effect in peripheral tissues since GnRH and its receptor are expressed in a wide variety of extra-pituitary tissues [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not detect apoptosis in somatotropes, gonadotropes or corticotropes we cannot rule out that LPS may induce apoptosis in other cell types of the anterior pituitary. It was suggested that rapid degradation of secretory vesicles makes it difficult to identify which cell types in this gland undergo programmed cell death (21,33). Hence, it is possible that any secretory cell at late stages of apoptosis, including lactotropes, could account for nonidentified apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%